Case Report: Postoperative cervical lymph node metastasis of the neuroendocrine carcinoma component of rectal mixed adenoneuroendocrine carcinoma - Quanwei, Gao; Yiqiang, Yin; Gangpu, Wang (Frontiers in Oncology, 2025)
IntroductionClinical case reports of rectal mixed neuroendocrine-non-neuroendocrine tumors are rare. This report highlights a case in which only the neuroendocrine carcinoma component metastasized to the lymph nodes seven years postoperatively, and its successful treatment.Case descriptionA 73-year-old male was admitted to our hospital in November 2015 with rectal bleeding lasting more than four months. A mass was detected and radical surgery and preventive ileostomy was performed, followed by six cycles of chemotherapy. Postoperative pathology revealed two distinct histological patterns, representing the adenocarcinoma and neuroendocrine components; 6 of 12 mesenteric lymph nodes tested positive, whereas 2 pelvic lymph nodes were negative. The patient presented again on April 30, 2022, with multiple palpable masses of varying sizes in the right side of the neck. A biopsy revealed a metastatic poorly differentiated carcinoma consistent with neuroendocrine carcinoma in the right cervical lymph nodes, which was considered to originate from the rectum. The patient again underwent surgery and six rounds of chemotherapy, which resulted in a significant reduction in the size of the cervical lymph nodes.DiscussionDue to the highly malignant nature of mixed adenoneuroendocrine carcinoma, early diagnosis and treatment are crucial for improving patient survival and therapeutic outcomes. A comprehensive, individualized treatment plan involving surgery, chemotherapy, targeted therapy, and immunotherapy can provide better patient outcomes. Given the metastatic potential of mixed adenoneuroendocrine carcinoma, long-term postoperative follow-up is essential.